Dynamics of Suitable Habitats for Typical Predators and Prey on the Qinghai‐Tibet Plateau Driven by Climate Change: A Case Study of Tibetan Fox, Red Fox, and Plateau Pika - Jingjie Zhang; Feng Jiang; Hongmei Gao; Haifeng Gu; Pengfei Song; Tongzuo Zhang (Ecology and Evolution)
ABSTRACT The Qinghai‐Tibet Plateau (QTP) is a biodiversity hotspot highly sensitive to global climate change. The Tibetan fox (Vulpes ferrilata), red fox (V. vulpes), and plateau pika (Ochotona curzoniae) are key species of the plateau, serving as typical representatives of predators and prey among its diverse wildlife. To evaluate the impact of climate change, we employed the maximum entropy model with 1237 distribution points and various environmental variables to predict habitat suitability under three global climate models and four representative concentration pathways for the 2050s and 2070s. The results revealed that the suitable habitats for two predators were projected to decline, with reductions ranging from 0.23% to 5.64% and 4.12% to 6.63%, respectively, with most reductions occurring in the central‐western and southern regions of the QTP. The decline was anticipated to be more pronounced in the 2070s compared to the 2050s. Conversely, the suitable habitat for prey species, plateau pikas, was expected to experience only a slight decrease (0.45%–0.98%) under scenarios of moderate greenhouse gas emissions. Habitat centroid analyses indicated a consistent northward migration of suitable areas for both predators and prey in response to climate change on the QTP. Furthermore, future overlap analysis between predator and prey habitats showed uncertain trends; however, the overlap between the Tibetan fox and Plateau pika habitats was notably lower compared to that of the red fox and plateau pika habitats. Regarding the current conservation efforts of both predators and prey, evaluation results highlighted the critical significant role of Sanjiangyuan National Park, China's first national park located in Qinghai Province, and Qiangtang Nature Reserve in Xizang as critical areas for the protection of these species on the QTP in China. The findings and methodologies of this research hold significant reference value for the conservation of predator and prey habitats in other global biodiversity hotspots.